Psychology and Modern Warfare Idea Management in Conflict and Competition - Taillard, Michael. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Throughout history, both military and commercial entities around the world have utilized these methods, and even since the formalization of psychological operations during WW2 our methods have improved greatly, but we are still only touching the 'tip of the iceberg', so to speak, of what is truly possible.